Asymptotics of the logarithmic derivative of an entire function of zero order - Zabolotskii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We find asymptotic formulas for the logarithmic derivative of a zero-order entire functionf whose zeros have an angular density with respect to the comparison function $v(r) = r^{λ(r)}$, where $λ(r)$ is the zero proximate order of the counting function $n(r)$ of zeros of $f$.